2019
DOI: 10.21037/atm.2019.04.16
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes following long GnRHa ovarian stimulation with highly purified human menopausal gonadotropin plus rFSH or rFSH in patients undergoing in vitro fertilization-embryo transfer: a multi-center randomized controlled trial

Abstract: Background: This clinical trial aimed to compare the clinical efficacy of highly purified human menopausal gonadotropin (HP-HMG) plus recombinant human follicle-stimulating hormone (rFSH) versus rFSH alone on controlled ovarian stimulation (COS) in vitro fertilization-embryo transfer (IVF-ET).Methods: A total of 610 women underwent long gonadotropin-releasing hormone (GnRH) agonist protocol for IVF treatment. The subjects were randomized into 2 groups: HP-HMG + rFSH group (n=305) and rFSH group (n=305). The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The discrepancy in the outcomes between the two protocols (GnRH agonist and GnRH antagonist) was attributed by the authors to the difference in the mechanism of each analog indicating the potential beneficial effect on the use of HMG in GnRH antagonist protocols in selected patients where mild stimulation is expected [15]. A recently published RCT that compared the efficacy of COS with highly purified (HP)-HMG plus rFSH versus rFSH alone in long GnRH agonist protocols showed that although the rFSH group was found with significantly increased retrieved oocytes, fertilization rates were higher in the HMG group whereas implantation and pregnancy rates were not different among the two groups [7]. Another systematic review by Levi Setti et al that presented the outcomes of studies comparing the administration of rFSH with HMG during COS observed that in the majority of included studies (10 out of 13), the number of retrieved oocytes was significantly higher in the rFSH group and the cost for both therapies was comparable [25].…”
Section: Efficacy Of Hmg In Cosmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrepancy in the outcomes between the two protocols (GnRH agonist and GnRH antagonist) was attributed by the authors to the difference in the mechanism of each analog indicating the potential beneficial effect on the use of HMG in GnRH antagonist protocols in selected patients where mild stimulation is expected [15]. A recently published RCT that compared the efficacy of COS with highly purified (HP)-HMG plus rFSH versus rFSH alone in long GnRH agonist protocols showed that although the rFSH group was found with significantly increased retrieved oocytes, fertilization rates were higher in the HMG group whereas implantation and pregnancy rates were not different among the two groups [7]. Another systematic review by Levi Setti et al that presented the outcomes of studies comparing the administration of rFSH with HMG during COS observed that in the majority of included studies (10 out of 13), the number of retrieved oocytes was significantly higher in the rFSH group and the cost for both therapies was comparable [25].…”
Section: Efficacy Of Hmg In Cosmentioning
confidence: 99%
“…Selection of the most appropriate regimen among uFSH and rFSH still remains challenging with the currently available literature reporting no significant differences in the number of oocytes retrieved or pregnancy rates among the two types of FSH [5,6]. The aforementioned gonadotropin preparations have been administered to support COS in infertile women who undergo ART protocols [7]. Hence, no consensus is available on the optimal regimens and preparations [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fresh embryo freezing or transfer was performed 3 or 5 days after fertilization. Whole embryo cryopreservation was carried out when the risk of ovarian hyperstimulation was high, and when the endometrium (thickness <7 mm) was not suitable for transplantation (13). Routine progesterone was given, and β-hCG was tested 2 weeks later to assess the pregnancy outcome.…”
Section: Stimulation Icsi Embryo Culture and Pregnancymentioning
confidence: 99%
“…ARTs are generally considered to be relatively safe; however, ARTs have been suggested to disturb epigenetic (re)programming during gamete and embryo development, which could have potentially adverse consequences on the epigenetic composition of the embryo (5)(6)(7). Recent studies have shown that ART may increase the risk of congenital disabilities, genetic imprinting disorders, and some childhood tumors (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%